2017
DOI: 10.4174/astr.2017.93.2.82
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the same technique-the same surgeon approach in the surgical treatment of pilonidal sinus disease: a retrospective cohort study

Abstract: PurposeAlthough there are several surgical methods for treatment of sacrococcygeal pilonidal sinus, there is no widespread consensus. In this study, we aimed to compare primary closure, Limberg, and modified Limberg flap techniques, with each performed by each of 3 surgeons.MethodsA total of 802 patients who were operated on for pilonidal sinus disease were included in this retrospective cohort study. Patients were evaluated in 3 groups: group 1 (limited excision + primary closure), group 2 (large excision + L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…at riskRR in % (95% CI)Nr. at riskPrimary open (143)2.7* (0.0–5.5)143*5.9* (1.4–10.4)120*NANANANA 32, 114, 118 Primary median closure (2902)0.8 (0.4–1.1)28187.0* (5.7–8.2)1383*18.8* (15.7–21.8)417*NANA 118, 127, 133, 136, 137, 139, 143, 148, 149, 158160, 169, 172174, 183, 192, 199– 201, 232, 242, 243, 246, 247, 597– 603 Primary asymmetric closure (727)1.7 (0.7–2.8)6212.5 (1.1–3.8)4037.4 (4.4–10.4)257NANA 183, 192, 253, 259, 261, 262 Karydakis/Bascom (2471)0.8 (0.4–1.1)23561.7* (1.1–2.4)1343*10.7 (7.4–13.9)257NANA 133, 172, 192, 199, 200, 262, 264, 267, 268, 270, 273, 274, 276, 279, 282, 284, 289– 292, 295, 296, 300, 305– 309, 603 Limberg/Dufourmentel (7653)0.1 (0.0–0.2)73691.1 (0.8–1.4)…”
Section: Resultsmentioning
confidence: 99%
“…at riskRR in % (95% CI)Nr. at riskPrimary open (143)2.7* (0.0–5.5)143*5.9* (1.4–10.4)120*NANANANA 32, 114, 118 Primary median closure (2902)0.8 (0.4–1.1)28187.0* (5.7–8.2)1383*18.8* (15.7–21.8)417*NANA 118, 127, 133, 136, 137, 139, 143, 148, 149, 158160, 169, 172174, 183, 192, 199– 201, 232, 242, 243, 246, 247, 597– 603 Primary asymmetric closure (727)1.7 (0.7–2.8)6212.5 (1.1–3.8)4037.4 (4.4–10.4)257NANA 183, 192, 253, 259, 261, 262 Karydakis/Bascom (2471)0.8 (0.4–1.1)23561.7* (1.1–2.4)1343*10.7 (7.4–13.9)257NANA 133, 172, 192, 199, 200, 262, 264, 267, 268, 270, 273, 274, 276, 279, 282, 284, 289– 292, 295, 296, 300, 305– 309, 603 Limberg/Dufourmentel (7653)0.1 (0.0–0.2)73691.1 (0.8–1.4)…”
Section: Resultsmentioning
confidence: 99%
“…We reported in this study no reccurence rate and only a case of Wound breakdown. In Kose, et.al., [13] study which included a total of 802 patients who were operated on for pilonidal sinus in many techniques {primary closure, Limberg, and modified Limberg flap techniques} The reccurence rate was about {12%} in average to all techniques used in the study . Traditional techniques have aimed to remove the area of chronic inflammation as well as any potential remaining nidus of infection, with healing achieved via secondary intention or primary coverage with surrounding tissue flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an investigation on the practice parameters of PS management reported 9 individual studies that showed the recurrence rates were reduced by 60% in those treated with midline and off-midline closure methods after excision [121718]. Kose et al [19] reported that off-midline closure techniques are superior to primary midline closure technique regarding general complication, wound dehiscence, and recurrence rates. Based on our favorable results, we firmly believe that excision of PS with minimal tissue loss through an incision away from the midline is justified.…”
Section: Discussionmentioning
confidence: 99%